Le patrimoine des arts du spectacle en France - Joël Huthwohl (In Situ)
Specialised libraries in the field of the performing arts play a particular and precise role in the constitution, conservation and interpretation of the performing arts heritage. Sharing their documentary missions, these institutions can include museums, libraries and archive centres. Their ambition is to collect the traces left by ephemeral performances, in all their diversity. These institutions benefit from the complementarity of the way they are specialised. They are sometimes called ‘library-museums’, a term which draws attention to the difficulty of defining an appropriate institution for the specific forms of memory that characterise the performing arts.